The approach of Community-Based Organizations in Stunting Management: A Case Study in Mentaya Hilir Selatan District, Kotawaringin Timur Regency - Gromiko; Hasanbasri, Mubasysyir (BKM Public Health and Community Medicine, 2024)
Purpose: Stunting is a serious public health issue in Indonesia, particularly in the Mentaya Hilir Selatan Subdistrict, Kotawaringin Timur Regency. This study aims to explore the role of Community-Based Organizations (CBO) in efforts to address stunting in the region. Methods: This research uses a qualitative case study approach with data collection techniques including in-depth interviews with 33 informants, observations, and document analysis. The study subjects consist of midwives, community health volunteers, members of the Family, Welfare Movement (TP-PKK), family planning cadres, mothers in the community, and program managers at the subdistrict/village level. Data were analyzed using content and thematic analysis methods. Results: The findings show that CBOs in Mentaya Hilir Selatan play a crucial role in handling stunting through various programs such as Pos Gizi Bunting , Posyandu, Aksi Cegah Stunting (ACS), Dahsyat (Dapur Sehat Atasi Stunting), and the Family Assistance Team (TPK). These programs involve activities such as nutrition education, cooking demonstrations, toddler weighing, and home visits to monitor the condition of pregnant women and young children. Conclusion: Community-based approaches through CBOs have proven effective in addressing stunting issues in Mentaya Hilir Selatan. The success of these programs is supported by good collaboration between various sectors, active community participation, and support from the government and related institutions.